Cork suberin as a new source of chemicals: 2. crystallinity, thermal and rheological properties - Cordeiro, N. (2021)
Suberin samples, obtained by alkaline methanolysis from cork (Quercus suber L.), were submitted to various physical characterizations; DSC, TGA, optical microscopy, density and rheological properties. A sub stantial proportion of these oligomers possessed a microcrystalline character with a melting range between 0 and 50°C. The amorphous part was liquid at room temperature and did not display a detectable glass transition upon cooling because of its wide molecular weight distribution. The viscous behaviour of suberin at room temperature was both plastic and thixotropic because of the structuring role of the microcrystals.